Tinjauan Hukum Islam Tentang Jual Beli Chip Game Online - Sunarsa, Sasa; Nurandini, Sri; Senjaya, Eko (Jurnal Hukum Ekonomi Syariah, 2025)
The buying and selling of online game chips involves transactions where the objects of sale cannot be physically handed over, but can instead be transferred digitally. These chips serve as virtual currency or tokens used in gameplay, and they have become a means for online game users to engage in business activities. This study seeks to answer the following research questions: What types of game chips are being traded in Sukarame Village, Bayongbong District? And what is the perspective of Islamic economic law on the buying and selling of online game chips? The purpose of this research is to identify the types of game chips traded in Sukarame Village, Bayongbong District, and to examine the Islamic economic law perspective regarding the online game chip trade. This study is categorized as field research and employs a qualitative descriptive approach. Data were collected through direct interviews with online game players. The findings indicate that the traded game chips are primarily from the online game Higgs Domino. Furthermore, the practice of buying and selling game chips in Sukarame Village, Bayongbong District, is considered invalid under Islamic law, as it does not fulfill the essential pillars and conditions of a valid sale and violates Islamic legal principles.  Keywords: Trading, Online Game Chips, Islamic Economic Law